An Alternative Approach to the Bedside Assessment of Left Ventricular Systolic Function in the Emergency Department: Displacement of the Aortic Root. (16th April 2013) - Ünlüer, Erden Erol; Karagöz, Arif; Bayata, Serdar; Akoğlu, Haldun; Stahmer, Sarah A.
Abstract Objectives Left ventricular ejection fraction (LVEF) is a crucial parameter in the management of patients with dyspnea in the emergency department (ED). The use of techniques other than echocardiography such as nuclear or magnetic resonance imaging to measure LVEF is unsuitable in the ED because of time constraints. This study aimed to compare echocardiographic aortic root (AR) excursion and LVEF measurement using the modified Simpson's method (biplane method of disks) as recommended by the American Society of Echocardiography. Methods After 2 hours of theoretical video and hands‐on training with 20 patients by an experienced echocardiographer, two emergency physicians prospectively evaluated patients with dyspnea. Two‐dimensional echocardiograms of the parasternal long‐axis view were obtained, and the displacement of the aortic root (DAR) was studied. M‐mode DAR recordings were obtained, and distances were measured as the maximized anterior displacement of the AR from the horizontal axis at end‐systole by using the leading‐edge methodology. LVEF was measured by an experienced cardiologist using the modified Simpson's rule. The sensitivity, specificity, positive and negative likelihood ratios (LR+, LR–), and positive and negative predictive values (PPV, NPV) were analyzed. A new formula for the prediction of the ejection fraction (EF) with the aid of DAR was then created. Results The mean (±SD) age with of the 70 study patients was 69.7 (±11.91) years. In these patients, DAR was highly correlated with EF (point biserial correlation coefficient = 0.79, p < 0.001) and one‐way analysis of variance (ANOVA) results were significant (F = 115.9; p < 0.001). The sensitivity was 94.4; specificity, 94.1; LR+, 16.6; LR–, 0.059; PPV, 94.4; and NPV, 94.1. Conclusions The results indicate that DAR is a sensitive index of left ventricular systolic function (SF) and can be used to reliably predict EF values using the rough formula of EF = 20 + 44 (DAR).